1998
DOI: 10.1262/jrd.44.141
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Ingestive Behavior and Plasma Metabolites by Estrogen in Ovariectomized Goats.

Abstract: Abstract. Ovariectomized goats were treated with subcutaneous implants containing ovarian steroid hormones and their effects on ingestive behavior and plasma metabolite concentrations were examined along with those on reproductive function. Sequential administrations of progesterone (P) and estradiol (E) reproduced steroidal milieu during the luteal through the follicular phases. Around 35 hours after the commencement of the E administration, estrous behavior appeared, and almost simultaneously the luteinizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The reproductive cycles of female goats were monitored by behavioral observation to avoid using females in estrus. The criteria for determining estrus by observing behavior were as described (Aoyama et al . 1998a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproductive cycles of female goats were monitored by behavioral observation to avoid using females in estrus. The criteria for determining estrus by observing behavior were as described (Aoyama et al . 1998a).…”
Section: Methodsmentioning
confidence: 99%
“…Three capsules each containing 0.1 g of Es made of silicon tubing (3.55 mm i.d., 4.65 mm o.d., 40 mm length: AS ONE, Osaka, Japan) were implanted into one animal. Published reports indicate that this method restores the blood concentration of Es to that of intact females (Aoyama et al . 1998a,b).…”
Section: Methodsmentioning
confidence: 99%
“…Pang et al [37] found that oestradiol and progesterone levels deceased on day 5 after ovariectomy in Huanghuai goats. In addition, Aoyama et al [38] indicated that the levels of oestrogen and progesterone concentrations declined to low values after 3 weeks in ovariectomized goats. In humans, the core body temperature corresponds with the level of female sex hormones, and it decreases with low level and increases with high level of female sex hormones [39].…”
Section: Effects Of Ovariectomy (Ovx) On Serum Urea Concentration In Adult Goatsmentioning
confidence: 99%